Bacteroides thetaiotaomicron Ameliorates Experimental Allergic Airway Inflammation via Activation of ICOS+Tregs and Inhibition of Th2 Response - Pang, Wenhui; Jiang, Yan; Li, Aifeng; Zhang, Jisheng; Chen, Min; Hu, Li; Li, Zhiyuan; Wang, Dehui (Frontiers in Immunology, 2021)
Inhibition of allergic airway diseases (AAD) by immunomodulation of the adaptive immunesystem through restoration of the enteric dysbiosis is an emerging therapeutic strategy. Patients with allergic rhinitis (n=6) and healthy controls (n=6) were enrolled, and gut microbiome composition analysis was performed by 16S rDNA sequencing. We also established an ovalbumin (OVA)-induced allergic airway inflammation murine model. Dysbiosis of the gut flora was observed in both AAD patients and the mice, with the decrease of the biodiversity and the quantity of the Bacteroidetes phylum. Oral application of Bacteroides (B.) thetaiotaomicron ameliorated the symptoms of OVA-induced airway hyperresponsiveness (AHR) and attenuated the airway inflammation in mice. In addition, nasal lavage fluid (NALF) and bronchoalveolar lavage fluid (BALF) from AAD mice orally administered with B. thetaiotaomicron showed reduced numbers of immune cells, and diminished secretion of T helper (Th)-2 cytokines (IL-4, IL-5, and IL-13) compared with the corresponding control mice, whereas the levels of Th1 cytokineIFN γ was not changed in both the groups.When B. thetaiotaomicron was co-administered with metronidazole in AAD mice, the immunomodulatory effect was weakened and the allergic inflammatory response was aggravated. The ratios of CD4+Foxp3+ cells, CD4+ICOS+ T cells, CD4+ICOS+ Foxp3+ regulatory T cells and IL-10-expressing CD4+Foxp3+ cells were increased in lymphocytes of spleen, mesenteric and cervical lymph nodes of AAD mice administrated with B. thetaiotaomicron. Therefore, our data indicate that oral administration of B. thetaiotaomicron effectively inhibited the development of AAD in murine model; inhibition was mediated by the activation of Tregs and inhibition of Th2 response without promoting a Th1 response.